Physical, structural, elastic and optical investigations on Dy3+ ions doped boro-tellurite glasses for radiation attenuation application - Bassam, S.A.; Naseer, K.A.; Keerthana, V.K.; Teresa, P. Evangelin; Sangeeth, C.S. Suchand; Mahmoud, K. A.; Sayyed, M. I.; Alqahtani, Mohammed S.; Shiekh, E. El; Khandaker, Mayeen Uddin * (Elsevier, 2023)
A set of Dy3+ ions doped boro-tellurite glasses is prepared using the melt quenching method and its radiation resisting aptitude is estimated through various structural and elastic features. The results were interpreted due to the effect of TeO2 concentration in the glass systems. The observed molar volume (Vm) values reduced with the rise in the tellurium content with the creation of more bridging oxygens in the structure. The cross-link density rises the rigidity of the glass and its density. Additionally, boron-boron separation and tellurium-tellurium separation, and optical band gap were computed to prove the connectivity of the system which is noted to reduce with the rise in the tellurium content. Glass with 40% TeO2 is observed to hold high elastic moduli and consequently high density and connectivity which are vital requirements for effective radiation shielding. Moreover, the Monte Carlo N-Particle transport code version 5 is used to qualify the γ-ray shielding properties. The qualification of the shielding properties showed that the linear attenuation coefficient was enhanced by a factor of 80% from 0.248 cm